Challenges and strategies for establishing inclusive school in Indonesia: Aligning Islamic values with inclusive education principles - Luqmanul Hakim Muttaqin; Muhammad Haekal; Ibrahim Ibrahim; Ratna Tri Utami (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The global movement towards inclusive education has gained momentum in recent years, aiming to provide equitable education for all students, regardless of their abilities. Indonesia, in response to this transformative movement, has ratified an inclusive education policy, aiming to provide educational opportunities to students with disabilities within regular classroom settings. However, translating policy into practice poses significant challenges, with deeply entrenched medical model perspectives influencing public perceptions of individuals with disabilities.This article delves into the necessity of fostering a comprehensive understanding of and valuing diversity to support the establishment of an inclusive school environment in Indonesia. It explores the essential shift from the medical to the social model in understanding students with disabilities and highlights the significant role of beliefs and attitudes in shaping the implementation of inclusive education. Furthermore, it examines the alignment of Islamic values, particularly the